A Binary Integer Linear Programming Model for Fault Section Estimation in Electric Power Systems - Escoto, Esau Figueroa [UNESP] (2019)
A new method, based on binary integer programming, to solve the problem of fault section estimation in power systems is developed in this work. This optimization model is formulated based on a set of minimum covers, subject to logical protection constraints applied by electric power companies. Constraints of this formulation, compares protection relay alarms reported from the SCADA system with the expected states of the protection relay functions allocated in power system. Naturally, the proposed problem is a complex binary integer nonlinear programming model. In order to apply classical optimization techniques, this model is recast as binary integer linear programming model. Numerical results show the effectiveness, applicability and robustness of the presented strategy by using a 7-bus test system.